Governance of Rice Distribution Under the Food Supply and Price Stabilization Program (SPHP): A Study of The Partnership Between Village-Owned Enterprises (BUM Desa) and The State Logistics Agency (Perum Bulog) in Bojonegoro Regency - Luci Fransiska Puspita Ningrum; Tjitjik Rahaju; Firre An Suprapto (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The limited participation of Village-Owned Enterprises (Badan Usaha Milik Desa, hereafter BUM Desa) in national food distribution networks constitutes a critical governance challenge in Indonesia: as of 2024, only five of 419 BUM Desa in Bojonegoro Regency had established formal partnerships with the State Logistics Agency (Perum Bulog). This study examines the governance of the BUM Desa–Perum Bulog partnership under the Food Supply and Price Stabilization Program (Stabilisasi Pasokan dan Harga Pangan, SPHP), applying the Integrative Framework for Collaborative Governance developed by Emerson, Nabatchi, and Balogh (2012) in combination with the Matrix of Alliances and Conflicts: Tactics, Objectives, and Recommendations (MACTOR) analytical method. A descriptive qualitative design was employed; data were generated through in-depth interviews, non-participant observation, and document analysis, and were interpreted using the Miles, Huberman, and Saldaña (2014) interactive model. The findings show that, while the partnership is functionally operational, it remains predominantly transactional. Across the four collaborative dimensions, drivers are convergent and strong; principled engagement is top-down and lacks deliberative depth; shared motivation is grounded in an organically constructed track record of performance integrity; and capacity for joint action emerges as the weakest dimension, constrained by limited human resources, disproportionate logistical burdens, and the absence of shared standard operating procedures. MACTOR analysis confirms a high degree of interest convergence between Bulog and BUM Desa, yet indicates that collective capacity for joint action requires systematic institutional strengthening. The study contributes to collaborative governance scholarship by integrating a diagnostic (Emerson et al.) and a strategic-relational (MACTOR) framework at the village scale, and by evidencing how state–village institutional asymmetries reshape the operation of principled engagement and joint-action capacity in a Global South food-governance setting. Concrete, evidence-based recommendations are offered for Perum Bulog, BUM Desa, the Department of Community Empowerment and Villages (DPMD), village governments, the National Food Agency, and the Ministry of Villages.